2015
DOI: 10.2471/blt.14.141390
|View full text |Cite
|
Sign up to set email alerts
|

Participants’ understanding of informed consent in clinical trials over three decades: systematic review and meta-analysis

Abstract: ObjectiveTo estimate the proportion of participants in clinical trials who understand different components of informed consent.MethodsRelevant studies were identified by a systematic review of PubMed, Scopus and Google Scholar and by manually reviewing reference lists for publications up to October 2013. A meta-analysis of study results was performed using a random-effects model to take account of heterogeneity.FindingsThe analysis included 103 studies evaluating 135 cohorts of participants. The pooled proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
216
4
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(240 citation statements)
references
References 135 publications
12
216
4
4
Order By: Relevance
“…Studies show that this process has been insufficient to achieve its ethical goal, since children and adolescents do not understand a great deal of the information about the research in which they are involved 4,[12][13][14][15] . In this sense, obtaining the FPIC from these participants may represent failure of the principle of respect for people 16 , because it only formally fulfills the ethical determination to provide participants with information and clarification about the study.…”
Section: Children's Knowledge Of the Terms Of Informed Assentmentioning
confidence: 99%
“…Studies show that this process has been insufficient to achieve its ethical goal, since children and adolescents do not understand a great deal of the information about the research in which they are involved 4,[12][13][14][15] . In this sense, obtaining the FPIC from these participants may represent failure of the principle of respect for people 16 , because it only formally fulfills the ethical determination to provide participants with information and clarification about the study.…”
Section: Children's Knowledge Of the Terms Of Informed Assentmentioning
confidence: 99%
“…Although a number of interventions have been developed to improve clinical trial informed consent, nearly all focus exclusively on improving patients' knowledge [6,7]. Even with the implementation of such interventions, a recent meta-analysis found that participant understanding of important concepts essential for informed consent has not increased during the 3 decades of studies examined [4]. To improve cancer clinical trial decision quality, interventions must go beyond knowledge provision to address aspects such as preference deliberation and decision preparedness, guiding patients through the trial decision-making process [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…Many patients harbor therapeutic misconceptions about the aim of clinical trials [1,2] and overestimate benefits of standard treatment [3]. In a recent meta-analysis of 103 studies, more than 25% of clinical trial participants did not understand the nature of the study they were participating in or the voluntary nature of participation [4]. Only approximately 50%of participants understoodcentral trial concepts such asthe use of placebos or randomization [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esse processo desempenha um papel fundamental no estudo, pois afeta diretamente como os princípios éticos são aplicados na prática (TAM et al, 2015). …”
Section: A Pesquisa No Brasilunclassified